HOUSEHOLDS’ ABSORBABILITY AND ADAPTABILITY COPING CAPACITY TO THE IMPACT OF FLOOD DISASTER IN ILE-IFE, NIGERIA - Mobolaji, David; Atoyebi, Sola; Daramola, Oluwole (Farabi Journal of Social Sciences, 2025)
Purpose. The purpose of this study is to examine households’ absorbability and adaptability coping capacities in response to flood disasters in Ile-Ife, Nigeria. The research seeks to understand how coping strategies vary across different residential zones and how socioeconomic characteristics influence these variations. Design/methodology/approach. Residential areas in Ile-Ife were stratified into three developmental zones: core, transition, and suburban. Using a multistage sampling technique, a total of 493 household heads were selected. Data were collected and analyzed to assess households’ coping capacities in relation to flood hazards. Findings. The results revealed that both absorbability and adaptability coping capacities differed significantly across the three zones. These variations were strongly influenced by the socioeconomic characteristics of household heads. The suburban zone, in particular, demonstrated weaker adaptability, highlighting the vulnerability of residents in this area. Originality. This study contributes to disaster risk reduction literature by providing empirical evidence on the relationship between socioeconomic characteristics and coping capacity in a flood-prone Nigerian city. It emphasizes the need for targeted policies, especially in suburban areas, to improve pre-disaster management activities, such as identifying flood-prone locations and issuing early warnings to residents. Keywords: Flood Disaster, Coping Capacities, Households, Ile-Ife, Resilience